Water–air flow in straight pipes and across 90∘ sharp-angled mitre elbows. (September 2019) - Al-Tameemi, Wameedh T.M.; Ricco, Pierre
Abstract: Water–air flow in horizontal and vertical straight pipes and through 90 ∘ sharp-angled mitre elbows is investigated by visualizing the flow patterns by means of a high-precision camera and by measuring the pressure drop. The flow is studied in pipes with three diameters for about six hundred conditions of water–air flows, characterized by superficial velocities in the ranges of j L * = 0.3–1 m/s for water and j G * = 0.15–34 m/s for air. The portion of the pipe upstream of the elbow is always positioned horizontally, while the portion of the pipe downstream of the sharp bend is oriented horizontally or vertically with the flow moving upward. Plug, slug, slug-annular, and annular flows are visualized in horizontal straight pipes, while slug, churn, and annular regimes are recorded in vertical straight pipes downstream of the sharp bend. These patterns are well predicted by the Mandhane map (Mandhane et al., 1974) for horizontally oriented straight pipes and by the Hewitt–Roberts map (Hewitt and Roberts, 1969) for vertically oriented straight pipes. The changes of the flow patterns as the fluids pass through the mitre elbows are discussed. A multiple membrane flow structure is observed in the vertical upward flow at much higher Reynolds numbers based on the water superficial velocity than in the vertical downward case previously reported in the literature. A dimensional analysis is employed to obtain the non-dimensional parameters that describe the flows through the straight pipes and across the elbows. It is proved that a rigorous way to present the flow regimes and the pressure-drop coefficients of the water–air flow for a given geometry is the space of the Reynolds numbers based on the superficial velocities of air and water for fixed Froude number because the flow is incompressible and isothermal. By expressing the maps in scaled form, the prediction of the flow patterns along the straight portions of the pipe improves. The flow patterns through the elbows are expressed in terms of rescaled Mandhane maps, which, for the first time, simultaneously represent the flow patterns both upstream and downstream of the elbows. New pattern-based empirical correlations are obtained for the scaled pressure drops for the water–air flows through the horizontal and vertical pipes and through the elbows. The correlations are based on the flow patterns and do not rely on widely used prediction models, thereby predicting the pressure drop more accurately than the models presently available in the literature.